PREPARATION AND CHARACTERIZATION OF LIPOSOMAL DELIVERY SYSTEM OF NATURAL HEME PROTEIN - Katsai, Oleksii; Ruban, Olena (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of the present study was to develop and optimize the methods for preparation and characterization of the liposomal delivery system of natural heme protein. Methods: Cytochrome C containing liposomes (Cyt-LS) were prepared by high-pressure homogenization technique using phosphatidylcholine (PC) and dipalmitoyl phosphatidylglycerol (DPPG). Nanoparticles were characterized by using: dynamic light scattering, zeta potential measurements, scanning electron microscopy and HPLC. The specific activity was studied in vitro. Results: The study of homogenization regimes for obtaining unilamellar Cyt-LS was carried out. The selected temperature regime of homogenization was kept within 38–44 °С with optimal homogenization pressure of 800 bar. The obtained Cyt-LS were characterized by the main physicochemical parameters showed: Encapsulation efficiency 95.8±2.0%, Zeta potential-57±1.0 mV, pH-6.95±0.05. Phospholipid impurities had the following content: lysophosphatidylcholine-0.60±0.05% and free fatty acids-0.4±0.05%. The average particle diameter was 156±2 nm. Also, the size of Cyt-LS particles was confirmed by the ability of emulsion subjected to the sterilizing filtration with the preservation of its main physicochemical properties. Cyt-LS exhibit specific activity, similar to non-liposomal Cyt-C solution. Conclusion: The formulation of the liposomal delivery system of heme protein was successfully prepared using natural components and evaluated for different parameters.